Some physical properties of apricots and testing apricot sorting machines - Polyák, N. I.; Csizmazia, Z.; Szabó, Z.; Kiss, G.; E., E. (International Journal of Horticultural Science, 2012)
Examinations were carried out in the manipulating and packaging plant of Gyümölcsért Ltd, in Boldogkôváralja, to determine some physical properties of five apricot cultivars and to test the work quality of the apricot sorting machines. The size and the weight of the fruits were measured and two sorting machines were tested. The results are given in tables and diagrams. The conclusions are also summarised.